Geotechnical problems related to foundations for tall buildings (case studies) - Khoo, Say Keong; Balasubramaniam, A.S.; Tomiolo, Andrea; Ohta, Hideki; Lee Foundation, Singapore (Bangkok : Asian Institute of Technology, 1981)
Five case studies have been investigated and they cover the various aspects of the geotechnical considerations and geotechnical problems associated with the design and construction of the foundations and deep basements for tall buildings in Singapore. The foundations studied included raft foundation, large diameter bored pile foundation, and piled mat foundation while the methods of deep excavation investigated are braced sheet piles, anchored sheep piles and slurry trench diaphragm wall. Specialised constructional techniques such as the diaphragm wall construc tion, the large diameter bored piles and the Chemical Churning Pile (CCP) application are used to overcome specific geotechnical and site problems. Site constraints, economy of construction, local building regulations and the structural loading arrangement are important considerations in the design and selection of the types and methods of construction of foundation and deep excavation besides considering the soil conditions.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Tall buildings; Piling (Civil engineering)